Investasi Asing Langsung, Produktivitas, Utang Luar Negeri dan Pertumbuhan Ekonomi di Indonesia - Rahman Dano Mustafa; Malik Cahyadin; Rosmah Nizam (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2025)
This study examines the impact of foreign direct investment (FDI), productivity (PR), and external debt (ULN) on Indonesia's economic growth from 1993 to 2022. The findings, derived from the application of Autoregressive Distributed Lag and ECM models, indicate that FDI exerts a negligible and inconsequential influence over the long term, despite exhibiting a favourable impact in the immediate term. The findings indicate that productivity has a positive but insignificant effect, suggesting the necessity for additional time or other factors to facilitate a more measurable impact in the long run. While external debt has the most significant effect on long-term economic growth, with positive potential if allocated to productive projects, this research underscores the significance of effective debt management and support to enhance productivity and promote sustainable economic growth.